Exploring Decision-Making Skills in Science Education: A Systematic Review of Operational Definition and Instructional Trends - Suci Indah Putri (International Journal of STEM Education for Sustainability, 2026)
Decision-making skills are widely recognized as essential for preparing students to navigate complex societal and scientific issues, yet how these skills are defined and taught in science education remains fragmented. This systematic review examined 20 studies published between 2010 and 2025 to analyze how decision-making is defined and what components are emphasized, how the criteria of decision is developed, and the kind of instruction supports its development. The PRISMA selection process identified eight key components of decision-making: identify problem, collect scientific data and evidence, consider multiple perspectives, generate options, develop criteria, assess pros and cons, select and justify decision, and evaluate decision. The review revealed that developing criteria, one component of decision-making, often involves developing values-based criteria. Learning practices were dominated by discussions, group work, and worksheets, with limited use of simulations, debates, or digital tools. These findings provide a framework for understanding and teaching decision-making skills in science education. Future research should validate this framework in classroom contexts and explore its adaptability across diverse educational environments.